Proses Pendampingan Sertifikasi Halal dan Pembuatan NIB di Desa Lomaer Kecamatan Blega Kabupaten Bangkalan - Hildah Meliyana; M. Mahfid Ahnan; Nuris Pratama Putra; Dina Kamalia; Alan Su’ud Ma’adi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Halal certification assistance activities in Lomaer Village, Blega District, Bangkalan Regency aim to assist Micro, Small and Medium Enterprises (MSMEs) in obtaining halal certification for their products. Many MSMEs in the Bangkalan area, but do not yet fully have halal certification. The existence of a halal product guarantee issued by the MUI (Indonesian Ulema Council) will provide protection for the general public to realize that every product that is designated as halal is considered safe for consumption in accordance with Sharia principles in Islam. This activity uses methods ranging from observation by collecting data on MSME actors, holding halal certification socialization activities, as well as assisting with halal certification and making NIB for the mechanism for submitting halal labels until registered. There were 8 MSMEs who attended the socialization activity, but because the quota was limited, only two MSMEs were selected, namely